Java : software structures : designing and using data structures. - Lewis, John, 1963-; Chase, Joseph, ....- (Boston : Pearson, 2005)
The second edition of Java Software Structures embraces the enhancements of Java 1.5, where all structures and collections are based on generics. The framework of the text walks the reader through three main areas- conceptualization, explanation, and implementation, allowing for a consistent and coherent introduction to data structures. The addition of integrated case studies provides complete examples to aid readers starting with the problem statement, to design rationale, through full implementation. Readers will learn how to develop high-quality software systems using well-designed collections and algorithms.
Keywords: Gegevensstructuren; Java (programmeertaal).